Psikoedukasi Kelompok Lansia di Bukit Batu, Bengkalis dengan Pelaksanaan Expressive Art Therapy - Wina Diana Sari; Rachmayati Eka Safitri; Ersaliya Arezah; Rizdqi Akbar Ramadhan (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
In 2050, as many as 16% of the world’s population will be elderly individuals. Furthermore, around 14% of adults aged 60 years and over live with mental disorders. This number is quite large for the post-productive group, hence special attention is needed for the empowerment and welfare of the elderly. The number of elderly people in rural areas is greater than in urban areas in Riau Province, which is the basis for implementing psychoeducation and art therapy for elderly groups in the district of Bukit Batu, Bengkalis. Art therapy in the form of fitness exercises and coloring was welcomed enthusiasticly by the target group. It is hope that the following service activities can be replicated in other villages as a form of concern for the elderly group.